Relationship between Academic Qualification and Madrasah Accreditation with Community Interests in Madrasah Tsanawiyah Private Vocational School, Pematangsiantar City - Mahda Ahyana Lubis; Tien Rafida (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
This study aims to determine: 1) the relationship between the academic qualification with public interest in MTs Privat Pematangsiantar, 2) the relationship between accreditation madrasah with a public interest on MTs Privat Pematangsiantar, and 3) the relationship between academic qualifications and the accreditation madrasah together -similar to the public interest in private MTs Pematangsiantar. This research is a quantitative research, with a kind of correlation research. This study was conducted in eight (8) Private MTs Pematangsiantar namely MTsS MESRA, MTsS Khoirotul Islamiyah, MTsS Guppi, MTsS Madani Al Islamiya School, MTsS Ibnu Sina, MTsS Fathul Islamiyah, MTsS YPI, MTsS Al Khairiyah. The population is 992 people and the research sample is 277 people. The result showed : 1) a positive and significant correlation between the academic qualifications with the public interest that the value of the correlation coefficient is 0.248, 2) a positive and significant correlation between accreditation madrasah with the public interest that the value of the correlation coefficient is 0.571, and 3) a positive and significant relationship between the academic qualification and the accreditation madrasah with the public interest that the value of the correlation coefficient 0.574.